(untitled) - Dahl, Stephan (Thousand Oaks, 2015)
This book offers a critical evaluation of the theoretical frameworks that can be used to explain and utilise social media, and applies them to fun real-life examples and case studies from a range of industries, companies and countries. These include Unilever, Snickers, American Express, Volkswagen and Amnesty International, and span campaigns run across different platforms in countries such as China, Canada, Sweden and Singapore
Keywords: Tiếp thị internet,Xã hội truyền thông,Social media.,Internet marketing; Khía cạnh xã hội,Social aspects